1992
DOI: 10.1007/bf02599113
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach to the treatment of nicotine dependence in a medical center setting

Abstract: A nicotine-dependence treatment program can be implemented in a medical center setting by using a model that involves physician, patient, and nicotine-dependence counselor. The physician-referred and counselor-directed consultations are followed by a systematic relapse-prevention program. The counselors utilize behavioral approaches, the philosophy and principles of the addictive disorders field, and adjunctive pharmacologic therapy. The patients are chronic, heavy smokers who have had many previous quit attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Although this bodes well for the generalizability of laboratory samples, characteristics of the larger study protocol (e.g., the requirement to abstain from smoking overnight) and related sample characteristics (e.g., low income) may still limit the generalizability of our data. Indeed, although our sample is demographically similar to other smoking studies (e.g., Hughes, 2004;Hurt et al, 1992), it differs on demographic and smoking history variables from the enrollees in at least one earlier study of smokers with comorbid substance abuse. Specifically, Gulliver et al (1995) report on alcohol-dependent smokers who reported smoking more cpd, were older, and were more likely to be married.…”
Section: Discussionmentioning
confidence: 89%
“…Although this bodes well for the generalizability of laboratory samples, characteristics of the larger study protocol (e.g., the requirement to abstain from smoking overnight) and related sample characteristics (e.g., low income) may still limit the generalizability of our data. Indeed, although our sample is demographically similar to other smoking studies (e.g., Hughes, 2004;Hurt et al, 1992), it differs on demographic and smoking history variables from the enrollees in at least one earlier study of smokers with comorbid substance abuse. Specifically, Gulliver et al (1995) report on alcohol-dependent smokers who reported smoking more cpd, were older, and were more likely to be married.…”
Section: Discussionmentioning
confidence: 89%
“…A treatment plan individualized to the patient's specific needs is then developed based on the stage of readiness. 16 Treatment components include behavioral, chemical dependency, pharmacologic, and relapse prevention strategies.…”
Section: Nicotine Dependence Interventionmentioning
confidence: 99%
“…The Nicotine Dependence Center (NDC) at the Mayo Clinic (Rochester, Minn) has provided clinical services for treatment of nicotine dependence to more than 20000 patients since 1988. 16 Among adults who received a nicotine dependence consultation, the 6-month self-reported smoking abstinence rate was 22.2%. 17 The purpose of this investigation was to assess the tobacco use outcomes and baseline characteristics of 96 adolescents aged 11 to 17 years who received clinical services for treatment of nicotine dependence at the NDC during the period from 1988 to 1997.…”
mentioning
confidence: 99%